An Experimental Connectivity Performance of Simple Wireless Mesh Implementation Using Wireless Distribution System (WDS) - Muhammad, Dicky; Indah Hapsari, Gita; Andriana Mutiara, Giva (IJAIT (International Journal of Applied Information Technology), 2017)
Today wireless technology grows rapidly, especially in the field of telecommunications and communications. Computer networks now widely utilizes wireless. Wireless Mesh Network is one of the method which is use to communicate computer wirelessly. One important factor in application of wireless network is how to extend wireless signal coverage. Wireless Distribution System is one way to expand the wireless network by mean of wireless interconnection of access point on the network IEEE 8022.11. This study suggests how to build a simple wireless computer network using WDS technology and describes connectivity performance and its signal coverage. The test result of connectivity performance shows that the connectivity between two computers work properly for reliability and multi SSID testing. However, the connectivity was not success in multichannel testing. Furthermore the test result of coverage shows that the range of wireless signal coverage reaches 39 meters with different circumstance room.